2003
DOI: 10.1046/j.1440-169x.2003.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐Microseminoprotein‐related molecules may participate in formation of the mesoderm in the chick embryo

Abstract: It has previously been shown that human ␤ -microseminoprotein enhances development of mesodermal structures in the chick embryo. The present study was carried out to elucidate the mechanism of action of human ␤ -microseminoprotein in the chick embryo. ␤ -Microseminoprotein brought about significant modulation of expression of Brachyury in gastrulating embryos. In approximately 50% of the treated embryos, Brachyury expression was enhanced around the Hensen's node. These cells not only expressed higher levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Further analysis on the translated amino acid sequences of these genes showed that they all had a domain that was analogous to the prostatic secretory protein of 94 amino acids (PSP94) based on the topological similarities of the cysteine residues, so we designated them as PSP94-like genes (Fig 6C). It was reported that the PSP94 genes in vertebrates underwent rapid evolution, which resulted in an improvement of their functions in a wide range of biological activities, such as inhibition of tumor growth [46], activation of immunity [47], and mesoderm formation [48]. Taken together, their specific arrangement pattern and distinguished expression profiles strongly suggested that the PSP94-like genes might play a vital role in the regenerative abilities of A .…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis on the translated amino acid sequences of these genes showed that they all had a domain that was analogous to the prostatic secretory protein of 94 amino acids (PSP94) based on the topological similarities of the cysteine residues, so we designated them as PSP94-like genes (Fig 6C). It was reported that the PSP94 genes in vertebrates underwent rapid evolution, which resulted in an improvement of their functions in a wide range of biological activities, such as inhibition of tumor growth [46], activation of immunity [47], and mesoderm formation [48]. Taken together, their specific arrangement pattern and distinguished expression profiles strongly suggested that the PSP94-like genes might play a vital role in the regenerative abilities of A .…”
Section: Resultsmentioning
confidence: 99%
“…Since Brachyury is required for convergent extension during gastrulation, cell survival and mesoderm formation (Conlon and Smith, 1999), these growth-promoting processes could be enhanced when extra Brachyury is available. Interestingly, chick embryos treated with exogenous FGF at HH stage 4 show a significant reduction in the length of body axis and corresponding downregulation of Brachyury expression (Khot and Ghaskadbi, 2001) while ß-microseminoprotein has an exactly opposite effect (Karandikar and Ghaskadbi, 2003) indicating a direct correlation between the two. The response of frog Brachyury to insulin is different however, it is found to be down regulated (Chatterjee and Ghaskadbi, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This duration of treatment is sufficient to detect changes, if any, at the transcriptional level (Khot and Ghaskadbi, 2001;Karandikar and Ghaskadbi, 2003). The embryos were fixed in 4% paraformaldehyde at 4ºC overnight.…”
Section: Whole Mount In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…HH stage 4 embryos were cultured in vitro using single ring technique (New, 1955) with modifications as described before (Khot and Ghaskadbi, 2001;Karandikar and Ghaskadbi, 2003;Patwardhan et al, 2004). To study the fate of cells derived from HFRs, the cells were grafted on the cultured embryos.…”
Section: Grafting Of Cells On In Vitro Cultured Early Embryosmentioning
confidence: 99%